MMC-based low-temperature detector system of the AMoRE-Pilot experiment. (12th July 2017) - Kang, C S; Jeon, J A; Jo, H S; Kim, G B; Kim, H L; Kim, I; Kim, S R; Kim, Y H; Kwon, D H; Lee, C; Lee, H J; Lee, M K; et al.
Abstract: Metallic magnetic calorimeters (MMCs) are highly sensitive temperature sensors that operate at millikelvin temperatures. An energy deposit in a detector can be measured using an MMC through the induced temperature increase. The MMC signal, i.e., a variation in magnetization can then be measured using a superconducting quantum interference device. MMCs are used in particle physics experiments searching for rare processes as their high sensitivity and fast response provide high energy and timing resolutions and good particle discrimination. Low-temperature detectors consisting of molybdenum-based scintillating crystals read out via MMCs were designed and built to perform simultaneous measurements of heat and light signals at millikelvin temperatures. These detectors have been used in the advanced Mo-based rare process experiment (AMoRE) that searches for the neutrinoless double beta decay of 100 Mo. This article provides a detailed description of the MMC-based low-temperature detector system of the AMoRE-Pilot experiment which currently uses five crystals.